Editorial: is proton pump inhibitor use associated with worse outcomes in patients with liver abscesses? Authors' reply. Issue 8 (25th March 2018) - Bettinger, D.; Thimme, R.; Boettler, T.
Abstract : Linked Content This article is linked to Bettinger et al and Tabibian and Lindor papers. To view these articles visit https://doi.org/10.1111/apt.14512 and https://doi.org/10.1111/apt.14568 .